Cadaveric Evaluation of Myelinated Nerve Fiber Count in the Nerve to the Gracilis Muscle in Relation to Use as a Free Functional Muscle Transfer for Elbow Flexion - Mahmood, Bilal; Marshall, Danielle C.; Wolfe, Scott W.; Lee, Steve K.; Fufa, Duretti T. (Journal of Reconstructive Microsurgery, 2020)
Background Optimizing axon count is essential for successful nerve transfer surgery, and a donor-to-recipient axon count ratio greater than 0.7:1 has been associated with improved outcomes. A gracilis free functioning muscle transfer (FFMT) is an option to restore elbow flexion, but its axon count has not been evaluated. Our aim was to quantify the axon count of the nerve to the gracilis muscle.Methods The nerve to the gracilis was dissected in 10 fresh frozen adult cadaveric hindquarter specimens (four females and six males). The length of the nerve to the gracilis was measured and a biopsy taken. A validated histologic preparation technique was utilized, and axons were counted. The mean length and axon counts were calculated.Results The average axon count in the nerve to the gracilis was 818 (range = 684–1,000, standard deviation [SD] = 116). The average length was 98 mm (range = 81–115 mm, SD = 13 mm).Conclusion Our study found the average axon count in the nerve to the gracilis was 818. Prior literature suggests axon count ratio greater than 0.7:1 is associated with better clinical outcomes. Using data from prior studies, the spinal accessory, three intercostal, and two intercostal nerves are all sufficient for the transfer to the nerve to the gracilis with donor to recipient ratios of 1.7:1, 1.3:1, and 0.9:1, respectively.
Keywords: axon count; free functional muscle transfer; gracilis